Design and evaluation of a Women in American Medical Informatics Association (AMIA) leadership program. (22nd October 2021) - Grando, Adela; Ancker, Jessica S; Tao, Donghua; Howe, Rachael; Coonan, Clare; Johns, Merida; Chapman, Wendy
Abstract: The objective is to report on the design and evaluation of the inaugural Women in AMIA Leadership Program. A year-long leadership curriculum was developed. Survey responses were summarized with descriptive statistics and quotes selected. Twenty-four scholars participated in the program. There was a significant increase in perceived achievement of learning objectives after the program ( P < .0001). The largest improvement was in leadership confidence and presence in work interactions (modal answer Neutral in presurvey from 21 responses rose to Agree in postsurvey from 24 responses). Most (92% of 13) scholars clarified leadership vision and goals and (83% of 18) would be Very Likely to recommend the program to others. The goals of the program—developing women's leader identity, increasing networks, and accumulating experience for future programs—were achieved. The second leadership program is on its way in the United States and Australia. This study may benefit organizations seeking to develop leadership programs for women in informatics and digital health.